A method to the madness: Ontogenetic changes in the hydrostatic properties of Didymoceras (Nostoceratidae: Ammonoidea). Issue 2 (May 2020) - Peterman, David J.; Yacobucci, Margaret M.; Larson, Neal L.; Ciampaglio, Charles; Linn, Tom
Abstract: The seemingly aberrant coiling of heteromorphic ammonoids suggests that they underwent more significant changes in hydrostatic properties throughout ontogeny than their planispiral counterparts. Such changes may have been responses to different selective pressures at different life stages. The hydrostatic properties of three species of Didymoceras ( D. stevensoni, D. nebrascense, and D. cheyennense ) were investigated by creating virtual 3D models at several stages during growth. These models were used to compute the conditions for neutral buoyancy, hydrostatic stability, orientation during life, and thrust angles (efficiency of directional movement). These properties suggest that Didymoceras and similar heteromorphs lived low-energy lifestyles with the ability to hover above the seafloor. The resultant static orientations yielded a downward-facing aperture in the hatchling and a horizontally facing aperture throughout most of the juvenile stage, before terminating in an upward direction at maturity. Relatively high hydrostatic stabilities would not have permitted the orientation of Didymoceras to be considerably modified with active locomotion. During the helical phase, Didymoceras would have been poorly suited for horizontal movement, yet equipped to pirouette about the vertical axis. Two stages throughout growth, however, would have enhanced lateral mobility: a juvenile stage just after the formation of the first bend in the shell and the terminal stage after completion of the U-shaped hook. These two more mobile phases in ontogeny may have improved juvenile dispersal potential and mate acquisition during adulthood, respectively. In general, life orientation and hydrostatic stability change more wildly for these aberrantly coiled ammonoids than their planispiral counterparts.